OBSTACLES TO DISTANCE LEARNING IN PAI LESSONS AT SDN TAMANAN - Adib, M. Afiqul; T, Tasman (Yayasan Pendidikan dan Kemanusiaan Hurriah Aceh, 2023)
The purpose of this study is to explain what obstacles occur during the learning process during the COVID-19 pandemic at SDN Tamanan, Bantul. The method in this research is field research or field research which is then integrated with various related sources. The results of this study faced several obstacles in distance learning, such as: the ability to master technology, infrastructure, internet coverage, and the lack of budgetary provision from the government. The conclusion is that distance learning should be a learning solution in the future. However, for now it is felt by many parties that it is not feasible to implement it, especially in areas that lack proper internet access